2008
DOI: 10.1016/j.envpol.2008.05.011
|View full text |Cite
|
Sign up to set email alerts
|

The impact of vegetation on sedimentary organic matter composition and PAH desorption

Abstract: Relationships between sedimentary organic matter (SOM) composition and PAH desorption behavior were determined for vegetated and non-vegetated refinery distillate waste sediments. Sediments were fractionated into size, density, and humin fractions and analyzed for their organic matter content. Bulk sediment and humin fractions differed more in organic matter composition than size/density fractions. Vegetated humin and bulk sediments contained more polar organic carbon, black carbon, and modern (plant) carbon t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Thus, seas or lakes often act as a trap for PAHs and can provide insight about their fate in aquatic ecosystems [3][4][5][6][7]. Because of their potentially toxic, mutagenic, and carcinogenic properties, considerable efforts have been made to reduce PAH pollution in many countries [8,9]. Many studies have indicated that reconstruction of the PAH pollution history by investigating lacustrine core samples of sediments is helpful to understand pollution mechanisms and develop effective countermeasures [10][11][12].…”
Section: Introductionmentioning
confidence: 98%
“…Thus, seas or lakes often act as a trap for PAHs and can provide insight about their fate in aquatic ecosystems [3][4][5][6][7]. Because of their potentially toxic, mutagenic, and carcinogenic properties, considerable efforts have been made to reduce PAH pollution in many countries [8,9]. Many studies have indicated that reconstruction of the PAH pollution history by investigating lacustrine core samples of sediments is helpful to understand pollution mechanisms and develop effective countermeasures [10][11][12].…”
Section: Introductionmentioning
confidence: 98%
“…Soil B was collected from the farmland being vegetated for a long time, which may contain polar SOM and enable to dissolve into the aqueous phase during the washing process. Vegetated sediments had observed to contain more polar organic carbon and modern (plant) carbon, which could facilitate desorption of PAHs such as Phe from sediments (Nichols et al, 2008;Nichols and Musella, 2009). In this study, the color of supernatants belonging to Soil B washing systems was brownish-green, different from that attaining to Soil A and pure TX100 solutions, in which the color was transparent.…”
Section: Effect Of Soil Composition and Pah Propertiesmentioning
confidence: 67%
“…However, for Soil B washing solution, the spectrum changed a lot, especially the CeO stretching at 1100 cm À1 , C]C stretching at 1610 cm À1 , C-H n stretching of alkane groups at 2850e3000 cm À1 , CeH stretching of arenes at 3030 cm À1 and OeH stretching of CeOH at 3200e3550 cm À1 . The above functional groups are typical groups of polar SOM, which can dissolve into the aqueous phase, thus causing the increased stretching intensity (Chen et al, 2005;Nichols et al, 2008). In addition, Grasso et al (2001) reported that dissolved SOM by a nonionic surfactant Alfonic 1412-7 could enhance the desorption of PAHs from soil by accelerating PAH diffusion rate.…”
Section: Effect Of Soil Composition and Pah Propertiesmentioning
confidence: 97%